Time is on my side: relational contracts and aggregate welfare - Kukharskyy, Bohdan; Pflüger, Michael P. (Bonn, 2018)
"This paper develops a simple general equilibrium model which establishes a link between the patience of economic agents and the well-being of nations. We show that firms in long-term oriented countries can mitigate hold-up inefficiencies by engaging with their suppliers in relational contracting – informal agreements sustained by the value of future relationships. Our model predicts that countries with a higher level of patience will exhibit greater economic well-being and higher total factor productivity. We provide empirical evidence in line with the predictions of our theory."